The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1086/663832
|View full text |Cite
|
Sign up to set email alerts
|

Determining Seabird Body Condition Using Nonlethal Measures

Abstract: Energy stores are critical for successful breeding, and longitudinal studies require nonlethal methods to measure energy stores ("body condition"). Nonlethal techniques for measuring energy reserves are seldom verified independently. We compare body mass, size-corrected mass (SCM), plasma lipids, and isotopic dilution with extracted total body lipid content in three seabird species (thick-billed murres Uria lomvia, all four measures; northern fulmars Fulmarus glacialis, three measures; and black-legged kittiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 59 publications
2
33
1
Order By: Relevance
“…We used body mass rather than scaled mass index or size-adjusted mass, because scaled mass index does not predict energy stores ('body condition') in seabirds, including murres, and size-adjusted mass does not substantially improve predictability in murres (Jacobs et al 2012). For each parameter (mass and corticosterone), we constructed a general linear model with Sex, Colony and Treatment as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…We used body mass rather than scaled mass index or size-adjusted mass, because scaled mass index does not predict energy stores ('body condition') in seabirds, including murres, and size-adjusted mass does not substantially improve predictability in murres (Jacobs et al 2012). For each parameter (mass and corticosterone), we constructed a general linear model with Sex, Colony and Treatment as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid analyses followed established protocols and standards [57], [34]. Briefly, plasma was added to Folch reagent (2∶1 v/v) and filtered [57].…”
Section: Methodsmentioning
confidence: 99%
“…High levels of circulating neutral lipids are associated with high energy expenditure (chick-rearing murres [26]; small fish [31]; birds [27], [32], [33]. Plasma neutral lipid level is associated with parental mass loss during chick-rearing [34], as lipids are mobilised to fuel increased energy spent flying, and parental mass during chick-rearing is negatively correlated with the mass gain of chicks [35], [36]. Plasma lipids are potentially a better measure of energy mobilisation than body mass because changes in body mass can represent changes in non-lipid portions [37], [26].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that body water pool derived 18 O using the plateau method has the highest correlation with actual amount of body water pool (Jacobs et al, 2012). Therefore, in our study, N o and R dilspace determined by the plateau method were used for the calculation of metabolic rates using the one- and two-pool models.…”
Section: Methodsmentioning
confidence: 99%